Seroprevalence of human T-lymphotropic virus HTLV and its associated factors in donors of a blood bank of Medellín-Colombia, 2014-2018 (2023)
Background Research on HTLV in Colombia is limited; despite being an endemic country there are few studies on the magnitude of this infection. The aim of this study was to determine the seroprevalence of HTLV I/II and its associated factors in donors to a blood bank of Medellín Colombia, 2014-2018. Methods This is a cross-sectional study of 52,159 donors with a secondary information source. Seroprevalence of HTLV I/II was determined with its confidence interval and the population characteristics were described by frequency and summary measures. To explore the associated factors, Pearson's Chi square test, Mann-Whitney U test, crude odds ratios were used and they were adjusted by logistic regression in SPSS 25.0. Results 88% of the population lived in the metropolitan area, 68.5% belonged to the University. 76.2% were altruistic donors (unpaid donors who did not donate to a specific patient). 24.5% were repetitive (paid) donors. 75% of the donors were under 41 years old. The seroprevalence of HTLV I/II was 0.176% (95% CI = 0.139% -0.213%), being statistically lower in repetitive donors and men. Conclusion The seroprevalence of HTLV I/II infection in the studied blood bank is lower than that reported in other blood banks at the departmental and national levels. In Medellín, it was associated with the frequency of donation and gender, which is useful information for the hemovigilance programs of the city. © 2019 Cardona-Arias et al.